Improving Listening Skills Using Learning Video Media for Fifth Grade Students of SD Negeri 118 Bengkulu Utara - Lathifah Lamis; Eli Rustinar; Hasmi Suyuthi (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
From the results of initial observations made by the author at State Elementary School 118 Bengkulu Utara, researchers found that there was a lack of utilization of learning media and there were still many students who were less active during the learning process. This study aims to determine how the results of improving the student learning process using learning video media on short films to improve listening skills of fifth grade students of SD Negeri 118 North Bengkulu. This research uses quantitative methods with experimental research. The research subjects were grade V students totaling 22 students. Data collection techniques using One Group Pre Test - Post Test Design listening to the short film story "Windup" by Yibing Jiang. Data were analyzed using pretest and post-test scores listening to short films with SPSS statistical t-tests. The results showed that the improvement of listening skills using learning video media for grade V students of SD Negeri 118 North Bengkulu before treatment in the form of learning video media was 73% in the moderate category, while the improvement of listening skills using learning video media for grade V students of SD Negeri 118 North Bengkulu after treatment in the form of learning video media increased to 85% in the good category. From these data it can be concluded that the use of learning video media contributes to improving students' listening skills significantly.